1494Content Analysis and Predicting Survey Refusal: What Are Respondents' Concerns about Face-to-face Mental Health Survey?. (2nd September 2021) - Altwaijri, Yasmin
Abstract: Background: Previous studies suggest that refusals form the largest proportion of nonresponse for household surveys. As face-to-face household health surveys are uncommon in several countries, it might be advantageous for prospective surveys to preemptively tackle respondents' refusal to survey participation. Methods: Using contact history data from the Saudi National Mental Health Survey, we examined the relationship between social environmental factors, respondent characteristics, survey request concerns recorded by interviewers, and respondents' propensity to refuse to participate in the survey. Content analysis and logistic regressions were conducted. Results: Our findings suggest that urbanicity, region, socioeconomic status, age, and gender are associated with refusal. Patriarchal gatekeepers and specific survey-related concerns are more likely to lead to temporary refusals compared to final refusals. Conclusions: These results have implications for survey researchers employing similar recruitment and data collection methods, for example in tailoring refusal conversion strategies for interviewers to address concerns expressed by Saudi and/or culturally similar respondents. Key messages: Results might benefit studies considering similar methods and investigating sensitive issues, improve response rates, and combat the declining trend that potentially jeopardizes the quality of survey data collected.